(untitled) (Intent Research Scientific Journal, 2023)
In the course of the study the features of application of geo-information systems and technologies in the management of territories are disclosed. The definition of territorial information management systems as information systems for management of territories that provide processes for the development of optimal spatial solutions is based on the use of up-to-date, reliable and complex geo-information necessary for the implementation of the functions of management of the territory by local authorities.